Perceived Discrimination, Satisfaction with Life and Radicalization: Gender Differences - Del Pino-Brunet, Natalia; Gómez-Jacinto, Luís; Hombrados-Mendieta, Isabel; Salas-Rodríguez, Javier; Castilla Mora, Rosario (Routledge, Taylor&Francis Group, 2022)
The present study analyzes the effect of perceived discrimination on satisfaction with life and radicalization in adolescents. We hypothesize that perceived dis- crimination relates positively to the radicalization of adolescents, while satisfac- tion with life plays a mediating role in the negative effects of discrimination. We also suggest that gender has a modulating effect, since there are vast differences in the effects of perceived discrimination in girls and boys. Eighty-seven girls and 126 boys from a Spanish secondary school participated in the study, aged 15 to 25. Results show that perceived discrimination relates positively to radicalization in boys but not in girls. Conversely, discrimination relates negatively with satisfaction with life in girls, but not in boys. The mediating effect of this variable barely relates to radicalization in either gender; however, gender does show a modulating effect, which can be seen in the differences found between boys and girls: perceived discrimination relates positively with radicalization in boys but not in girls; conversely, it relates negatively with satisfaction with life in the case of girls but not in boys. These findings highlight the importance of achiev- ing an appropriate integration of adolescents in society.
Keywords: Discriminación; Radicalismo; Satisfacción con la vida; Jóvenes